Identification of thermostable peptide markers in meats using gel-based fractionation coupled with mass spectrometry - Mat Junoh, Nadiah (2018)
Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) followed by mass spectrometry is widely used in proteomic study mainly in meats due to their effectiveness and efficiency in generating reliable data. An alternative method such as enzyme-linked immunosorbent assay (ELISA), although known to be highly-specific but it bears the risk of cross-reactivity. The genomic approach is another commonly used method but suffers from potential deoxyribonucleic acid (DNA) contamination from other organism and due to its structure, DNA molecule is less resistant to heat treatment. The limitation of these methods may lead to a false positive result in detection analysis. First, the purpose of this study was to compare the electrophoretic pattern of proteins in one-dimensional (1DE) and two-dimensional (2DE) gel electrophoresis in meat derived from cow, water buffalo, pig and wild boar upon different heat treatments. Then, the next aim was to screen the species-specific thermostable protein markers in all species using principal component analysis (PCA) and partial least square-discriminant analysis (PLS- DA). The third aim was to identify the thermostable protein and peptide markers obtained from electrospray ionization liquid chromatography-mass spectrometry (ESI-LC-MS) and matrix-assisted laser desorption ionization time-of-flight/time-of-flight tandem mass spectrometry (MALDI-TOF/TOF-MS/MS). The meats were subjected into several heat treatments which were (1) chilled at 4℃ for 30 min, (2) roasted at 150℃ for 20 min, and (3) fried at 160℃ for 6 min, before subjecting to two different combinations of proteomic approaches i.e. SDS-PAGE coupled with ESI-LC-MS and 2DE coupled with MALDI- TOF/TOF-MS/MS. The extracted proteins were fractionated using 1DE gel electrophoresis coupled with combined multivariate analysis of PCA and PLS-DA for grouping and discriminative analysis. The pattern of electrophoretic proteins in all species was similar but differences appeared between the raw and cooked meats. The potential thermostable protein markers derived from all species were determined using ESI-LC-MS. At the molecular weight of 55.06 kDa, proteins that have been identified from cow samples were tropomyosin, moesin, cadherin, and septin. As for water buffalo, 5-oxoprolinase has been identified at the molecular weight of 181.22 kDa. In the pig, serum albumin, calpain-7, and ATP synthase subunit alpha, mitochondrial were identified with the molecular weight of 77.02 kDa while wild boar has shown to have cathepsin K and calcium/calmodulin-dependent protein kinase type II subunit delta at the molecular weight of 48.61 kDa. These approaches were successful in providing preliminary data analysis for the screening of thermostable protein markers with species- specificity. For the second approach, tropomyosin was selected and analyzed using 2DE gel electrophoresis followed by MALDI-TOF/TOF-MS/MS. Minor differences were observed in the amino acids sequences in both tropomyosin (TPM) isoforms i.e. TPM2 and TPM1 for each species. Moreover, several thermostable peptides that were found to belong to the Bovidae family were HIAEDSDR and LDKENAIDR and Suidae family, RIQLVEEELDR. These potential peptides could be used as markers to discriminate between Bovidae and Suidae families. Thus, the result indicated that these isoforms have the potential to be selected as thermostable species-specific protein and peptide markers in meat authentication.